Effective elimination of 4‐nitrophenol in water by reduced graphene oxide/CoFe2O4/Fe nanocomposite - Thao, Vu Dinh; Sinh, Nguyen Dinh; Dung, Nguyen Trung; Toan, Vu Ngoc; Nguyen Nhat Huy (Vietnam Journal of Science and Technology, 2025)
There is great potential for practical applications of visible-light photocatalysts with magnetic and Fenton-like properties. In this study, a reduced graphene oxide/cobalt ferrite/zero valent iron (rGO/CoFe2O4/Fe) ternary material was synthesized by combining co-precipitation, hydrothermal, and reduction with NaBH4. The as‐prepared rGO/CoFe2O4/Fe nanocomposite was characterized by FTIR, XRD, UV-Vis DRS, VSM, SEM, EDX, Raman, and BET analyses. As a result, rGO sheets were effectively covered with a high density of CoFe2O4 and Fe0 (40 – 100 nm) nanoparticles. The rGO/CoFe2O4/Fe exhibited outstanding properties such as high saturated magnetization (31.18 emu/g at 11 kOe) with superparamagnetic property, high 4‐nitrophenol (4‐NP) degradation efficiency (98.78%), fast removal rate (k = 0.0361 min−1), and narrow band gap energy (1.327 eV). As an excellent magnetic visible-light photo-Fenton-like catalyst, rGO/CoFe2O4/Fe nanocomposite has the potential for practical applications in wastewater treatment.